Assessment of Doshpaka and Dhatupaka Lakshana in Evaluation of Sadhyasadhyatava (Prognosis) of Diseases as Diagnostic Methodology (AYUSHDHARA, 2024)
Ayurveda is an ancient art of healing which is accepted worldwide. It has its own principals and unique diagnostic treatise. Ayurveda describes four types of disease on the basis of prognosis and emphasizes the importance of knowledge of prognosis for successful management of diseases. Before initiating any treatment in a patient the assessment of prognosis of disease is very important. There are many basic principles for evaluation of Sadhyasadhyatva one of them is Doshpaka and Dhatupaka. It is described by Madhavacharya in Jwara Nidan Adhyaya. The knowledge of Pakwa Doshas and symptoms of Doshapaka will help the physician to make appropriate choices in treatment and follow the chronology of treatment. The Doshapaka is an indicator for reversal of disease process. Similarly, it is very important for the physician to know about Dhatupaka i.e., tissue/cellular destruction and its role in formation of diseases. The knowledge of tissue/cellular destruction and its symptoms would be helpful for physician to plan a proper protocol of treatment and to control destruction and suppuration of tissues/cells. This critical review insight on how the evaluation of Doshapaka and Dhatupaka Lakshana helps in assessment of Sadhya-asadhyatva of disease.